The Role of Bioenergetic Supervision in Bioenergetic Training - Munroe, Alex (Bioenergetic Analysis, 2022)
Supervision plays a key role in a trainee’s movement towards certification as a Bioenergetic Therapist. It is therefore important to clearly understand and discuss the components of Bioenergetic supervision. Some commonalities for supervision in psychology, social work and Bioenergetic Analysis are set out. Aspects of supervision that are unique to Bioenergetic Analysis are identified. The paper concludes with an exercise to help the reader experience some of the Bioenergetic concepts presented. The paper is a beginning attempt to contribute to this discussion.